Pelatihan Penggunaan Aplikasi DUOLINGO Dalam Pembelajaran Bahasa Ingris Siswa Kelas XII SMK YPUI Parung - Pari Purnaningsih; Resti Isnaeni; Devi yunita (APPA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Learning English encompasses skills such as speaking, writing, reading, and listening. Students often struggle with understanding English lessons due to monotonous, teacher-centered teaching models. To boost students' motivation, teachers need to employ creative methods, such as using learning applications that can make the classroom atmosphere more enjoyable. One application that supports English learning is Duolingo. Duolingo is an online language testing application that is engaging and not boring, supporting various skill levels and accessible via desktop and mobile. With this application, users can learn anytime and anywhere. Based on this background, lecturers from the Informatics Engineering program plan to hold a training session on using Duolingo as a medium for learning English at SMK YPUI Parung. This training is provided by Pamulang University for free and is attended by 10-30 students from SMK YPUI Parung. It is hoped that the participants of this training can create learning media at school and become more motivated in learning English.